EFEK SUDUT KEMIRINGAN UNTAI SIMULASI SIRKULASI ALAMIAH TERHADAP RUGI TEKANAN DI SEPANJANG PIPA - Gaos, Yogi Sirodz (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2015)
EFFECTS OF SIMULATION strand tilt angle NATURAL CIRCULATION OF LOSS IN ALL THE PRESSURE PIPE. Have been made to optimize the energy utilization efficiency, performed in addition to designing up a new energy conversion devices, as well as utilize natural laws that act as natural circulation phenomena. Experimental studies conducted to understand the natural phenomenon of circulation by calculating the pressure loss based on temperature changes in the cold and the heat in the USSA strand FT-02. USSA construction consists of FT-02 components of SUS 304 pipe 1 inch in diameter, heater, cooler and expansion tank. Experimental variation is the height difference between the hot side and cold side based on the variation of the angle of the strand, which is 30o, 60o and 90o or cooler altitude of 0.275 meters, 0.476 and 0.550 meters. Outlet temperature of the heater (TH) and the outlet of the cooler temperature (TC) is used as a parameter to be measured and on-record with a time span of the experiment for 40 minutes. Experimental results and calculations using multiple correlation showed, the pressure loss will have price stability in a row bar is 0.000044, 0.000063 and 0.00021 bar bar by changing the angle of 30o, 60o and 90o, while the influence of water mass flow rate led to an increase of 0.002626 (kg / s) to 0.01487 (kg / s). The effect of the forces that affect the loss of pressure has different characteristics for each of the difference in height cooler and heater.Keywords: angle, flow rate, pressure loss